Fizetési mérleg: a gazdaságpolitika mostohagyereke - Botos, Katalin (Közép-Európai Közlemények, 2013)
Magic triangle, magic four, magic six: there are different conflictic economic policy aims. In contemporary economy the public enemy No1 is unemployment in the developed and emerging countries. To create jobs states support consumption and the housing industry by lowering interest rate. Banking industry also contributed to the booming housing business by expanding crediting, sometimes on external resources. In the USA resources were created by securitization. Here, too, was important capital inflow. Financial investments in the new financial innovation were booming til 2008. The crises led to bust in housing business and the whole world economy. constructing industry the leading economic branch got in troubbles, housing prices fell. Only excessive state involvement helped to avoid the Great Depression. One root of the problems is neglecting the balance of payments problems, and the too large reliance on external resources. Balance of payments was a stepchilde of economic policy. Key words: economic policy unemployment, financial innovation, growth, housing, credit expansion, external resources, balance of payments.